2009
DOI: 10.1128/iai.00436-09
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbiota of Women with Frequent Vulvovaginal Candidiasis

Abstract: Vulvovaginal candidiasis (VVC) is an insidious infection that afflicts a large proportion of women of all ages, and 5 to 8% of affected women experience recurrent VVC (RVVC). The aim of this study was to explore the possible importance of vaginal bacterial communities in reducing the risk of RVVC. The species composition and diversity of microbial communities were evaluated for 42 women with and without frequent VVC based on profiles of terminal restriction fragment polymorphisms of 16S rRNA genes and phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 45 publications
6
80
0
3
Order By: Relevance
“…66 Zhou et al 67 reported the absence of a clear difference between the vaginal microbiota of women with a history of RVVC and healthy controls, and suggested that the vaginal microbiota does not protect against infection. However, studies comparing microbiota composition do not generally incorporate functional aspects of the microbiota that can be very relevant for the differential production of lactic acid and other anti-Candida metabolites impacting mucosal reactivity.…”
Section: The Vaginal Microbiotamentioning
confidence: 99%
“…66 Zhou et al 67 reported the absence of a clear difference between the vaginal microbiota of women with a history of RVVC and healthy controls, and suggested that the vaginal microbiota does not protect against infection. However, studies comparing microbiota composition do not generally incorporate functional aspects of the microbiota that can be very relevant for the differential production of lactic acid and other anti-Candida metabolites impacting mucosal reactivity.…”
Section: The Vaginal Microbiotamentioning
confidence: 99%
“…Progesterone has the suppressive effect on the anti-Candida activity of neutrophils, while estrogen level had been found to reduce the ability of vaginal epithelial cells to inhibit the growth of C. albicans; and estrogen decreases immunoglobins in vaginal secretions resulting in increased vulnerability of pregnant women to VC. 6 Furthermore, the efficacy of the VITEK-2 system and the conventional method for identification of Candida sp. after culturing of clinical samples were compared herein.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is a frequent companion of pregnancy, which gets complicated jeopardizing health of mother and child. 5,6 Women with gestational diabetes are more likely to develop VC and vulvo-vaginal candidiasis (VVC), because of elevated sugar levels encouraging overgrowth of fungi. 7,8 9,10 This study gives has a comparative account of a tedious, traditional and inexpensive method, the slide culture technique with the advanced, accurate and expensive method of diagnosis, the VITEK-2 automated system.…”
Section: Introductionmentioning
confidence: 99%
“…Their sample size was very small though. Studies have shown that alteration of or abnormal vaginal bacterial flora predispose to RVVC only in the presence of antibiotic use [58,59]. It is worth noting thought that the majority of women who receive antibiotics do not develop genital candidiasis and majority of women with genital candidiasis have not used antibiotics in the immediate past.…”
Section: Antibiotic Therapymentioning
confidence: 99%